Hypertrophic pachymeningitis with sarcoidosis: a rare cause of craniocervical compression - Subrati, Nagina (BMJ Case Rep, 2015)
We describe a case of a 58-year-old woman with a suspected dural tumour. She presented with progressive pyramidal weakness. MRI confirmed compression of the medulla oblongata and spinal cord at the level of C1–3. The localised dural mass lesion homogenously enhanced on T1 MRI and was considered most likely to be a meningioma. Incidentally, CT scan of the chest revealed peribronchial soft tissue thickening, suggestive of pulmonary sarcoidosis. Owing to the progressive nature of her weakness, she had a posterior occipitocervical decompression with a C1–3 laminectomy and resection of the thickened dura. Histology showed densely collagenous tissue with scanty psammoma bodies and multinucleate giant cells, consistent with hypertrophic pachymeningitis (HP)—a rare, chronic inflammatory condition, characterised by thickening and fibrosis of the dura. This case demonstrates that masses in the craniocervical junction can be varied in pathology and when there is evidence of systemic inflammation, HP should be considered.